Precipitation variability in Portugal from 1960 to 2011 - Nunes, Adélia de Jesus Nobre (2015)
This study analyses spatial variability and trends in annual and monthly precipitation (amount and concentration) based on data from 42 stations in mainland Portugal during the period 1960–2011. Relationships between certain geographic variables (elevation, latitude and longitude) and precipitation variability were also determined in order to check for specific dependencies and spatial patterns in precipitation distribution, concentration and changing trends. Trends and relationships have been analysed using both parametric and non-parametric tests. The results showed that annual precipitation had decreased in all stations and that this trend is statistically significant for most of the time series (70% of the stations showed negative trends with at least a 0.1 significance level). The Annual Precipitation Concentration Index revealed an opposite behaviour pattern, suggesting that even though the annual trend for precipitation amount was negative overall, more than half of the udometric stations registered a more marked seasonality for precipitation during the period 1960–2011. However, only one station showed statistical significant time trend. Regarding the influence of geographical features, latitude is the most important variable, governing spatial distribution and variations in annual precipitation as well as its intra-annual changeability. These important changes in precipitation, involving both amount and concentration, may have severe consequences for ecosystems and societies.